$A = \left ( \dfrac{1}{2} - 1 \right ) \left ( \dfrac{1}{3} - 1 \right )... \left ( \dfrac{1}{2002} - 1 \right ) \left ( \dfrac{1}{2003} - 1 \right ) \\
= \left ( - \dfrac{1}{2} \right ) \left ( - \dfrac{2}{3} \right )... \left ( - \dfrac{2001}{2002} \right ) \left ( - \dfrac{2002}{2003} \right ) \\
=(-1)^{2003 - 2 + 1} \left ( \dfrac{1}{2} . \dfrac{2}{3} ... \dfrac{2001}{2002} . \dfrac{2002}{2003} \right ) \\
= (-1)^{2002} . \dfrac{1}{2} . \dfrac{2}{3} ... \dfrac{2001}{2002} . \dfrac{2002}{2003} \\
= \dfrac{1}{2} . \dfrac{2}{3} ... \dfrac{2001}{2002} . \dfrac{2002}{2003} \\
= \dfrac{1}{2003}$